Factores de riesgo del deterioro de la integridad cutánea en zonas de presión, presentes en pacientes con pérdida de la movilidad, en usuarios del Hospital José María Velasco Ibarra De Tena. Año 2015 - Rodríguez Bosquez, Magali Hortencia (2016)
The purpose of this research was to determine the risk factor the deterioration of skin integrity cutaneous, in pressure zones present in patients with loss of mobility. It applies the technique of the questionnaire survey as a tool and instrument observation as observation guide 19 patients to gather information applies. The design was cross fixed descriptive, bibliographic and field. The following results were obtained population, with higher prevalence of pressure ulcers, It was the biggest 65s with 42.11%, male with 68.42%, indigenous ethnic group with 52.63%, from rural to 78.95%, the prevailing level of primary schooling with 52.63%, the prevalence is 7.11%, the most common location is in the sacral region with 26.31%, stage III with 52.63%, granulation tissue injury 26.31%, type of hematic secretion 26.31%, surface 5-8 cm with 31.58%, 36.84% have pain, disoriented mental state with 26.31%, with 47.37% immobility, with urinary incontinence and fecal 47.37%, with 31.58% occasionally incomplete nutrition, not roams with 47.37%; immobility imposed with 15.79%, up bed inadecuathe 84.21%, 42.11% dry skin; ignorance of the caretaker with 36.84%, high risk level 52.64%. It is concluded that pressure ulcers are prevalent in higher percentage in bedridden patients with loss of mobility, unconscious, poor nutrition, with urinary and fecal incontinence and that do not have permanent care of a person.- The author conducted educational activities through conferences and educational workshops Keywords: Risk Factors, Deterioration, Skin Integrity, Pressure Areas, lost mobility